Security communities and the habitus of restraint: Germany and the United States on Iraq - Bjola, C; Kornprobst, M (2007)
Borrowing from Norbert Elias, we introduce the habitus of restraint to the study of security communities. This habitus constitutes a key dimension of the glue that holds security communities together. The perceived compatibility of practices emanating from the habitus that members hold fosters the collective identity upon which a security community is built. The violation of a member's habitus by the practices of another member, however, disrupts the reproduction of collective identity and triggers a crisis of the security community. Our analysis of Germany's reaction to Washington's case for war against. Iraq provides empirical evidence for the salience of the habitus for the internal dynamics of security communities.